Carbon dioxide gas emission, carbon sequestration and grain yield from soil amended with organic manures and fertilizer N in rice-wheat system - SINGH, Y. V.; SHARMA, S. K. (Journal of Soil and Water Conservation, 2020)
A field experiment was conducted at ICAR-IARI, New Delhi for two years (2014-16) with rice-wheat cropping system to estimate carbon dioxide gas emission, carbon sequestration and yield potential of soil amended with different organic manures. The experiments were laid out in a randomized block design in rice and wheat crops comprising two tillage treatments viz. puddled and non-puddled in rice and tillage and no-tillage in wheat. The crop nutrition treatments included seven fertilizer treatments including recommended doses of N through urea (120 kg N ha-1) and integrated use of urea + FYM @ 5.0 tha-1, urea + green manure @ 5.0 tha-1, urea + vermicompost@ 3.0 tha-1. Results showed that addition of organic manures resulted in an increase in CO2 gas emissions. Cumulative seasonal emissions of CO2-C ranged from 397 to 796 kg ha-1 in the mineral fertilized and combine use of mineral fertilizers and manures. The CO2 emissions reduced by 28 to 37% in no-tillage compared to traditionally tilled wheat. The seasonal emissions of CO2 varied from 438-683 kg CO2-C ha-1 in the mineral fertilizer and its combination with manures under no-tillage wheat. The addition of organic manures resulted in additional sequestration of soil C in rice-wheat cropping system. Carbon content was enhanced under reduced tillage conditions of soil. However, the emission of CO2 gas increased with addition of organic manures.